United Kingdom : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper aims to provide European Union (EU), while recognizing that the choice of whether to remain in the EU is for U.K. voters to make and that their decisions will reflect both economic and noneconomic factors. The question of EU membership is both a political and an economic issue, and the referendum has sparked a wide-ranging debate on the United Kingdom's role in the EU. Given the range of plausible alternative arrangements with the EU, the number of channels by which countries could be affected and the range of possible effects on the United Kingdom and other economies are broad.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet